Impact of respiratory viral infections during pregnancy on the neurological outcomes of the newborn: current knowledge - Manti, Sara; Spoto, Giulia; Nicotera, Antonio Gennaro; Di Rosa, Gabriella; Piedimonte, Giovanni (Frontiers in Neuroscience, 2024)
Brain development is a complex process that begins during pregnancy, and the events occurring during this sensitive period can affect the offspring’s neurodevelopmental outcomes. Respiratory viral infections are frequently reported in pregnant women, and, in the last few decades, they have been related to numerous neuropsychiatric sequelae. Respiratory viruses can disrupt brain development by directly invading the fetal circulation through vertical transmission or inducing neuroinflammation through the maternal immune activation and production of inflammatory cytokines. Influenza virus gestational infection has been consistently associated with psychotic disorders, such as schizophrenia and autism spectrum disorder, while the recent pandemic raised some concerns regarding the effects of severe acute respiratory syndrome coronavirus 2 on neurodevelopmental outcomes of children born to affected mothers. In addition, emerging evidence supports the possible role of respiratory syncytial virus infection as a risk factor for adverse neuropsychiatric consequences. Understanding the mechanisms underlying developmental dysfunction allows for improving preventive strategies, early diagnosis, and prompt interventions.